Strategi Kepemimpinan Kepala Sekolah dalam Upaya Pengembangan Mutu Sumber Daya Manusia (Studi Kasus Sekolah Dasar Pemulutan) - Noptario, Noptario; Mamonto, Rubi; Shaleh, Shaleh (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2023)
The role of the principal in improving human resources in schools is very important. This is because the role of a leader who goes well in schools will produce solutive policies and be able to answer the problems that exist in schools. This is the background for researchers to raise the issue of the principal's leadership strategy in efforts to develop the quality of human resources. This study used a qualitative research method with data collection techniques through interviews. Interviews were conducted with 3 informants consisting of school principals, teachers, and business administration staff. The data analysis technique used in this study is the data analysis technique with the Miles and Hubermans theory, namely by reducing data, presenting data and drawing conclusions. There are several obstacles encountered by the Pemulutan Elementary School principal in efforts to develop the quality of their human resources, including the large number of senior teachers, inadequate school facilities and infrastructure and the location of the school which is quite far from urban areas. However, the Pemulutan Elementary school principal made several strategies so that the quality of the school's human resources could increase, the things that were done by the school principal in developing school human resources were teaching material policies, opening discussion rooms, reward and punishment and conducting training and guidance for teachers to become a professional teacher and be able to keep up with the times.